Notes on the differences between Fredlanea and Eulachnesia, and description of a new species (Coleoptera, Cerambycidae, Lamiinae, Hemilophini) - Galileo, Maria Helena M.; Santos-Silva, Antonio (Zootaxa, 2016)
During the process of identification of some specimens sent to the late Ubirajara Ribeiro Martins de Souza by Miguel Angel Monné, we came across some problems involving the genera Fredlanea Martins & Galileo, 1996 and Eulachnesia Bates, 1872. Herein we try to make clearer the differences between those two closely related genera. Actually, only a single good and constant difference could be found between those genera, as shown below.